Canadianising the Holocaust: Debating Canada’s National Holocaust Monument - Chalmers, Jason (Canadian Jewish Studies / Études juives canadiennes, 2016)
This paper addresses Canada’s first national monument to the Holocaust: the National Holocaust Monument (NHM) in Ottawa. I examine how public discourse surrounding the NHM constructs the Holocaust as a Canadian memory. Political spokespersons create connections between the Holocaust and Canadian history by drawing on themes of Canada’s Allied role during the war, post-war Jewish immigration, and the narrative of None Is too Many. The discourse frames Canada as both a hero and villain in respect to the Holocaust. Whereas some nations seek to resolve such conflicting memories, Canadians seem content to remember their nation in both ways.